Coaction and upward social comparison reduce the illusory conjunction effect support for distraction - Muller, Dominique; Atzeni, Thierry; Butera, Fabrizio ([Place of publication not identified] Elsevier, Inc., 2004)
This article proposes an integration of Festinger's (1954) social comparison theory and Baron's (1986) distraction?conflict theory of the social facilitation?inhibition effect, which successfully predicts attentional focusing in coaction when social comparison represents a distraction. Two experiments confronted participants with the illusory conjunction task (Treisman, 1998), where illusions occur because of the lack of attentional processing of central cues. If coaction, like upward comparison, is distracting and thereby enhances the attention allocated to central cues (here the target's features) at the expense of peripheral cues (here distractors), then a reduction should be found in the illusions. Experiment 1 indeed showed a lower rate of conjunctive errors under upward comparison than under downward comparison. Experiment 2 specified that this effect was due to downward comparison effectively reducing distraction, with upward comparison only maintaining it, as compared to mere coaction.
Includes bibliographical references.
Keywords: Social comparison; Social facilitation